2022
DOI: 10.21873/invivo.12792
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Influence of the Lymph Node Ratio on Lymph Node Metastasis-positive Gastric Cancer Patients Who Receive Curative Treatment

Abstract: Background/Aim: The present study investigated the clinical impact of the lymph node ratio (LNR) on overall survival (OS) and recurrence-free survival (RFS) in cancer patients with lymph node metastasis who received curative treatment. Patients and Methods: Eighty-six patients who received curative surgery for gastric cancer between 2000 and 2015, and in whom lymph node metastasis was pathologically confirmed, were included in this study. The LNR was defined as the ratio of the number of metastatic lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although LNM was the direct reason for distant metastases, it reflects the biological selection of more aggressive subpopulations showing close relation with local and/or regional recurrence [ 3 , 4 ]. As demonstrated by many researchers, the presence of LNMs is associated with decreased postoperative survival in gastric cancer [ 5 , 6 ], being the most important prognostic factors [ 7 ]. Because the increased rate of early detection in gastric cancer can lead to an improved prognosis, the concentrations on improving patients' quality of life and utilizing minimally invasive treatments have increased [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although LNM was the direct reason for distant metastases, it reflects the biological selection of more aggressive subpopulations showing close relation with local and/or regional recurrence [ 3 , 4 ]. As demonstrated by many researchers, the presence of LNMs is associated with decreased postoperative survival in gastric cancer [ 5 , 6 ], being the most important prognostic factors [ 7 ]. Because the increased rate of early detection in gastric cancer can lead to an improved prognosis, the concentrations on improving patients' quality of life and utilizing minimally invasive treatments have increased [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we showed that the LNR was a more appropriate LN system for assessing patient prognosis. Despite similar findings reported in prior studies (53)(54)(55)(56)(57)(58)(59), some of which also utilized data from the SEER database (54,58), our study possesses some distinct characteristics that differentiate it from earlier research. We collected SEER data from 2010 to 2020.…”
Section: Discussionmentioning
confidence: 59%
“… 1 Currently, radical GC surgery is the only means to cure locally progressive GC; however, lymph node (LN) metastasis in most GC patients greatly affects survival and prognosis. 2 4 LN metastasis is an independent risk factor for tumor recurrence after radical GC surgery, and standardized and thorough LN dissection is directly related to the clinical prognosis of GC patients. Therefore, strengthening intraoperative LN tracing and dissection is the key direction of GC treatment.…”
Section: Introductionmentioning
confidence: 99%